Joint analysis of m6A and mRNA expression profiles in the testes of idiopathic nonobstructive azoospermia patients - Tang, Qiuqin; Wu, Wei; Lu, Yiwen; Zhou, Yijie; Wu, Wangfei; Li, Jinhui; Pan, Lianjun; Ling, Xiufeng; Pan, Feng (Frontiers in Endocrinology, 2022)
Background: Growing evidence has indicated that epigenetic factors might be associated with the pathophysiology of idiopathic nonobstructive azoospermia (iNOA). As the most common RNA modification, N6-methyladenosine (m6A) methylation has recently attracted more attention in the regulation of spermatogenesis; however, its role in the mechanisms of iNOA is still unclear. Objective: To determine the differential expression of mRNA and m6A methylation status in the testes of iNOA patients. Methods: Testes tissues from diagnosed iNOA and controlled obstructive azoospermia (OA) patients were collected and grouped according to the histological examinations. Total RNA was isolated and quantified by an m6A RNA Methylation Quantification Kit. The expression level of mRNAs was detected by qRT-PCR analysis. Differentially expressed m6A genes were analyzed using the human ArrayStar m6A epitranscriptomic microarray, and bioinformatics analyses were applied. Results: A total of 36 iNOA and 8 controlled patients were included. The global expression of m6A in the iNOA group was significantly decreased. A dosage relationship was observed between the m6A decline and the degree of impaired spermatogenesis, with the successive process of normal spermatogeneis, hypospermatogenesis (HP), maturation arrest (MA), and Sertoli cell-only syndrome (SO). Four down-expressed genes (BDNF, TMEM38B, RPL3L, and C22orf42) displayed significantly lower expression of m6A methylation. Additionally, they also showed a gradually down-expressed tendency in the three groups (OA, HP, SO/MA groups). Moreover, m6A reader EIF3A was approved to have differential expression through microarrays analysis, which was consistent with the result from the qRT-PCR test. Conclusions: The m6A expression was gradually downregulated in the testes tissue from iNOA patients in accordance with the degree of spermatogenic dysfunction. The determined differential expression of mRNA and m6A methylation status may represent potentially novel molecular targets for the mechanism study of iNOA in the epigenetic level, which could benefit the understanding of the pathophysiology of iNOA.